Effects of rock fragment cover on hydrological processes under rainfall simulation in a semi‐arid region of China. Issue 6 (15th February 2018) - Xia, Lu; Song, Xiaoyu; Fu, Na; Cui, Shengyu; Li, Lanjun; Li, Huaiyou; Li, Yaolin
Abstract: Rock fragment cover has long been an important agricultural crop production technique on the Loess Plateau, China. Although this approach plays an important role in controlling hydrological processes and preventing soil erosion, inconsistent results have been recovered in this field. In this study, we investigated the effects of rock fragment cover on infiltration, run‐off, soil erosion, and hydraulic parameters using rainfall simulation in the field in a semi‐arid region of China. Two field plots encompassing 6 rock fragment coverages (0%, 10%, 20%, 25%, 30%, and 40%), as well as 2 rock fragment positions and sizes were exposed to rainfall at a particular intensity (60 mm h −1 ). The results of this study showed that increasing the rock fragment coverage with rock fragments resting on the soil surface increased infiltration but decreased run‐off generation and sediment yield. A contrasting result was found, however, when rock fragments were partially embedded into the soil surface; in this case, a positive relationship between rock fragment coverage and run‐off rate as well as a nonmonotonic relationship with respect to soil loss rate was recovered. The size of rock fragments also exerted a positive effect on run‐off generation and sediment yield but had a negative effect on infiltration. At the same time, both mean flow velocity and Froude number decreased with increasing rock fragment coverage regardless of rock fragment position and size, whereas both Manning roughness and Darcy–Weisbach friction factor were positively correlated. Results show that stream power is the most sensitive hydraulic parameter affecting soil loss. Combined with variance analysis, we concluded that the order of significance of rock fragment cover variables was position followed by coverage and then size. We also quantitatively incorporated the effects of rock fragment cover on soil loss via the C and K factors in the Revised Universal Soil Loss Equation. Overall, this study will enable the development of more accurate modelling approaches and lead to a better understanding of hydrological processes under rock fragment cover conditions.